2018
DOI: 10.1109/tnsre.2018.2843884
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Nintendo Wii Balance Board for the Assessment of Balance Measures in the Functional Reach Test

Abstract: The functional reach test (FRT) is widely used for assessing dynamic balance stability in elderly and pathological subjects. Force platforms (FPs) represent a fundamental part of the instrumented FRT experimental setup due to the central role of center-of-pressure (COP) displacement in FRT analysis. Recently, the nintendo wii balance board (NBB) has been suggested as a low-cost and reliable device for ground reaction force and COP measurement in poorly dynamic motor tasks. Therefore, this paper aimed to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
1
13
0
2
Order By: Relevance
“… 11,13–16 The Nintendo Wii Balance Board (NBB) was utilized in two studies, both of which demonstrated its suitability for assessing dynamic balance. 15,16 Mengarelli et al 15 found a high correlation between the NBB and an instrumented dynamic force platform (Bertec 4060H, 60x40 cm) in both the anterior-posterior and medial-lateral directions (r > 0.990). The root-mean-square error values for center of pressure displacements were 1.14 ± 0.88 mm and 0.55 ± 0.28 mm in the anterior-posterior and medial-lateral directions, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“… 11,13–16 The Nintendo Wii Balance Board (NBB) was utilized in two studies, both of which demonstrated its suitability for assessing dynamic balance. 15,16 Mengarelli et al 15 found a high correlation between the NBB and an instrumented dynamic force platform (Bertec 4060H, 60x40 cm) in both the anterior-posterior and medial-lateral directions (r > 0.990). The root-mean-square error values for center of pressure displacements were 1.14 ± 0.88 mm and 0.55 ± 0.28 mm in the anterior-posterior and medial-lateral directions, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Mengarelli et al 15 also used the functional reach test to establish the validity of the NBB for assessing dynamic balance. The validity of the NBB was evaluated by comparing it to a laboratory-grade force plate.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of [29] performed tests related to the Functional Reach Test with people with non-mentioned diseases with the Nintendo Wii Balance Board for the measurement of the center-of-pressure path deviation. It was used to recognize three activities, such as reaching down, reaching up, and walking, and five types of fall, such as backward-fall, left-fall, right-fall, forward-fall, and non-fall.…”
Section: Healthy Peoplementioning
confidence: 99%
“…Os jogos descritos visam aos ajustes posturais anteroposteriores e látero-laterais e coordenação de membros inferiores, assim como controle de equilíbrio e coordenação, os quais influenciam diretamente no desempenho da marcha. 12,13 Os dados obtidos foram analisados descritivamente, pelo programa Excell ® 2010.…”
Section: Métodosunclassified